(3LjH GdYQhS hQjMGf GdfahSs - (3eMeO Hf CMeO Hf SYjO GdJejej, CHh YHO Gddg,fMh (B390 (3g`s
(3ChdgG (B:s
(3hHYO aeLJeY ai gPg GdfSNI CehQ YXjeI Yf GdYHGS QVi Gddg Yfg hYf hdOg hYf LejY GdUMGHI Bejf UaI Ogf ddbhHI s
(3BNQgG (B:s
(3HGH UHZ dhf, dhf GdPgH WQja MSf ef cJGH EHf GdYHGS aEfgG JYTH hJHjV aj oLeYJjf GhKdGK Ef TGA Gddg s
(3GdcQGSGJ GdChdis
(3HNW MOjKs
(3hfTY GdMHQ aj HYV GdUaMGJ hLGA Ydi GdfSNI(B: (3LjH GdYQhSs
(3hQjMGf GdfahS s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B264s
Keywords: (3GdWHs